Safety, tolerability, pharmacokinetics and pharmacokinetic-pharmacodynamic modeling of cetagliptin in patients with type 2 diabetes mellitus - Zhou, Chen; Zhou, Sufeng; Wang, Jie; Xie, Lijun; Lv, Zhanhui; Zhao, Yuqing; Wang, Lu; Luo, Huan; Xie, Daosheng; Shao, Feng (Frontiers in Endocrinology, 2024)
Aims: To evaluate the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of cetagliptin (CAS number ：2243737-33-7) in Chinese patients with type 2 diabetes mellitus (T2DM). A population PK/PD model was developed to quantify the PK and PD characteristics of cetagliptin in patients.Materials and methods: 32 Chinese adults with T2DM were enrolled in this study. The subjects were randomly assigned to receive either cetagliptin (50 mg or 100 mg), placebo, or sitagliptin (100 mg) once daily for 14 days. Blood samples were collected for PK and PD analysis. Effects on glucose, insulin, C-peptide, and glucagon were evaluated following an oral glucose tolerance test (OGTT) (day15). Effects on HbA1c and glycated albumin (GA), and safety assessments were also conducted. Meanwhile, a population PK/PD model was developed by a sequential two-step analysis approach using Phoenix.Results: Following multiple oral doses, cetagliptin was rapidly absorbed and the mean half-life were 34.9-41.9 h. Steady-state conditions were achieved after 1 week of daily dosing and the accumulation was modest. The intensity and duration of DPP-4 inhibition induced by 50 mg cetagliptin were comparable with those induced by sitagliptin, and 100 mg cetagliptin showed a much longer sustained DPP-4 inhibition (≥80%) than sitagliptin. Compared with placebo group, plasma active GLP-1 AUEC0-24h increased by 2.20-and 3.36-fold in the 50 mg and 100 mg cetagliptin groups. A decrease of plasma glucose and increase of insulin and C-peptide were observed following OGTT in cetagliptin groups. Meanwhile, a tendency of reduced GA was observed, whereas no decreasing trend was observed in HbA1c. All adverse events related to cetagliptin and sitagliptin were assessed as mild. A population PK/PD model was successfully established. The two-compartment model and Sigmoid-Emax model could fit the observed data well. Total bilirubin (TBIL) was a covariate of volume of peripheral compartment distribution (V2), and V2 increased with the increase of TBIL. Conclusions: Cetagliptin was well tolerated, inhibited plasma DPP-4 activity, increased plasma active GLP-1 levels, and exhibited a certain trend of glucose-lowering effect in patients with T2DM. The established population PK/PD model adequately described the PK and PD characteristics of cetagliptin.